2021
DOI: 10.3389/fpsyt.2021.673089
|View full text |Cite
|
Sign up to set email alerts
|

Immersive Virtual Reality Simulation in Forensic Psychiatry and Adjacent Clinical Fields: A Review of Current Assessment and Treatment Methods for Practitioners

Abstract: Background: Research has indicated that interactive, computerized case simulations using immersive virtual reality (VR) technology may be beneficial in the augmentation of conventional methods of assessment and treatment in forensic psychiatry, primarily through providing an engaging and safe environment in which the user can practice and learn skills and behaviors. However, there does not appear to be an overview of current developments available in the field, which may be an obstacle to clinicians considerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 37 publications
2
26
0
Order By: Relevance
“…One feasibility study has been conducted in the field of forensic psychiatry since the first research by Renaud et al in offenders with a pedophilic disorder ( 46 , 47 ). In this study, Fromberger and colleagues tested, in pedophilic sex offenders, whether coping behaviors in VR risk scenarios—encountering children asking for help in a supermarket—can provide additional information for risk assessments ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…One feasibility study has been conducted in the field of forensic psychiatry since the first research by Renaud et al in offenders with a pedophilic disorder ( 46 , 47 ). In this study, Fromberger and colleagues tested, in pedophilic sex offenders, whether coping behaviors in VR risk scenarios—encountering children asking for help in a supermarket—can provide additional information for risk assessments ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interventions involving VR have been particularly emphasized as promising eHealth applications in forensic settings (Fromberger et al, 2014), and have been suggested to bridge the gap between real life and laboratory experiences and thus increase the ecological validity of psychological research (Kisker et al, 2019). A recent systematic review (Sygel and Wallinius, 2021) demonstrated promising developments in adjacent fields (e.g., treatment of psychosis), however only a few methods, focusing on simulations of realistic offenserelated stimuli in the assessment and treatment of deviant sexual interests (Renaud et al, 2005;Benbouriche et al, 2014;Renaud et al, 2014;Fromberger et al, 2018), have been evaluated for forensic settings so far. In relation to aggression, only two methods employing VR have been described: the VR Game for Aggressive Impulse Management VR-GAIME (Smeijers and Koole, 2019), developed as a complement to ART interventions, and the VR Aggression Prevention Training for forensic psychiatric patients (VRAPT; Tuente et al, 2018; described in detail below).…”
Section: Virtual Reality In Forensic Settingsmentioning
confidence: 99%
“…A substantial amount of literature shows that participants exhibit realistic responses to virtual situations in terms of physiological, emotional, cognitive, and even behavioral reactions (for a review on the topic, see Slater and Sanchez-Vives, 2016 ). For this reason, VR is increasingly being used in psychological therapy (see Cieślik et al, 2020 , for a recent systematic review) and has even been used in the field of forensic psychology (see Sygel and Wallinius, 2021 for a recent review) and for work with sexual offenders ( Benbouriche et al, 2014 ). Recent work in our research group has investigated the use of VR in the area of intimate partner violence (IPV), with two main purposes.…”
Section: Introductionmentioning
confidence: 99%